Constitutionality of President’s Authority Regarding Lockdown Policy During the State’s Emergency - Wahid, Deny Noer; Ramadhan, Febriansyah; Utami, Tasyabilla Pandi (The Indonesian Journal of International Clinical Legal Education, 2022)
The Article 22 of the 1945 Constitution of the Republic of Indonesia grants an exclusive authority to the president enacted as "legal dictatorial power", meaning that the President holds a sovereign authority to create and form regulations or laws independently without needing to discuss with the House of Representatives (DPR). The authority is to stipulate Government Regulation in Lieu of Law (Perppu). It refers to the president’s authority basis to run the regulation over the running government whose primary aims are to guarantee and to protect the citizen’s welfare. On the other hand, in respect of Indonesian constitutional system that adheres to the concept of decentralization, local governments also have the right to determine a situation/condition in response to the global pandemic situation. As a matter of the fact, so many overlaps are found in the exercise of policies and regulations under the authority of central and regional governments. Thus, the current research is aimed to strengthen the role of President as the head of state in dealing with the global pandemic issue and in applying lockdown with its all mechanisms. Practically, the research was carried out by means of normative legal research method associated with statutory, conceptual, historical, and comparative approaches. Furthermore, the research had found that the President appeared to be the supreme power holder over central governments, equipped with strong legitimacy in running the lockdown in accordance with juridical and empirical perspectives on the effectiveness of pandemic handling